Handout Matematika berbantuan Etnomatematika Berbasis Budaya Lokal - Aini, Elma Purnama; Masykur, Ruhban; Komarudin, Komarudin (Desimal: Jurnal Matematika, 2018)
This study aims to develop teaching materials in the form of handouts through a local culture-based ethnomathematics approach to the wake-up material. The research model used is the research of Borg and Gall development, but in this study only limited to seven steps of research and development, namely: 1) Potential and Problems; 2) Gathering information; 3) Product Design; 4) Design Validation; 5) Design Revisions; 6) Product Trial; and 7) Revision of the Ahir Phase. Data collection techniques used in this study, namely interviews, observation, and questionnaires (questionnaires). Data analysis techniques using descriptive qualitative analysis that describes the results of product development. Based on the result of data analysis, it is evaluated from the quality aspect of the prevalence of teaching materials to get the average score of 3.97 with the category of "Valid". While the learner's response to a limited trial earned an average grade of 3.67 with the "Practical" category, and the questionnaire response of learners on a large trial earned an average of 4.02 under the "Pull" category. It can be concluded that the developed teaching materials have valid, practical, and interesting criteria that can be used as teaching materials in teaching and learning activities.